Philosophy of History of Adam Ferguson and Immanuel Kant - ZÁKUTNÁ, Sandra (Faculdade de Filosofia e Ciências, 2015)
The paper compares central issues of philosophy of history of A. Ferguson and I. Kant. It deals with their explanation of origins and development of civil society, and characterizes its basic features, focusing on progress motivated by fruitful conflict and tension among individuals and nations. It also focuses on the role of citizens in civil society and the question of their activity. Then, in connection with Ferguson’s and Kant’s views on relationships among states the paper discusses their different portrayal of possible future history.